المفهوم الحديث للطرف في العقد - الساعدي جليل حسن; عبد الوهاب محمد (Journal of Legal Sciences, 2019)
The contact will be obligated as well as strong if it is contracted in right way. The contract is as the law in its obligation. Everyone must be followed the law so he /she must be obligated in the contract that he /she contracted. There is no clear suitable justification about the concept of partner in the contract that leads to this concept not to be stable. It becomes clearer when the idea of the group of contract appears. The idea of the group of contract in determination of the concept of partner is criticized by the jurisprudence. It tries to put a new concept for the partner in the contract or another one and also they have the same. The persons who have the adjective of partner should be having the same power which enjoy with the contracted partner in the contract.